Pemanfaatan Sistem Informasi Geografi dalam Menerapkan Pariwisata Cerdas di Kawasan Gunung Nona - Jasman Jasman; Masri Ridwan; Fuad Guntara (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
This study is to uncover the spatial potential that includes landscaping and areas in the Mount Nona Tourism Spasial, Enrekang Regency, South Sulawesi, Indonesia. Data collection methods by field survey, literature review and documentation. Data were analyzed qualitatively and quantitatively, processed using Arcgis 10.5. The results showed that the Mount Nona Tourism Area has fulfilled aspects of 4A tourism products, namely Attractiveness, Amenity, Accommodation and Comfort. While the potential for landscaping is located in the area of ​​5,219 ha which is administratively located in the Tanete, Mindante, Batu Noni, Bambapuang and Rosoan villages. The topography starts with a minimum height of 140 masl and a maximum of 1,540 masl. Villa Bambapuang, Dante Pine, Buttu Macca, Mandu Site, Goa Japan and Outbond Bambapuang. The movement of tourists throughout 2018-2019 are in all tourist attractions in the Mount Nona Region, with the highest hotspots. This study discusses the Regional Government for the Gunung Nona Tourism District District in the Provincial and National Tourism Development Strategic Plan.